Teaching geography in the context of secondary education from the perspective of teaching experience. - Jairo Antonio Cerón Diaz; Eliana Marcela Delgado Rangel (LÍNEA IMAGINARIA, 2025)
With the constitutional reform of 1991, the Colombian educational system began a process of modernization that, in addition to considering the physical or infrastructure component, also included the educational model in place at the time. The above involved adopting a new teaching-learning act whose pedagogical practices would transform the ways in which students would appropriate various knowledge. In this context, teaching geography represented for educators a more practical and experiential exercise, moving away from the traditional model, the ability to memorize, and the static placement of locations on a map; prompting the teacher to rethink their role within the classroom and the social impact of the knowledge they imparted to their students. Thus, Geography begins to propose a multitude of solutions to understand the complexity present in the various social, economic, and environmental processes that shape our world; responding to realities of both local and global order related to aspects such as citizenship, climate change, social inequality, accelerated urbanization, and other global challenges that affect geographic space. The following article presents a text for dissemination from the author’s personal perspective and the integration of literature on the teaching of Geography in the context of secondary education; its objective is aimed at generating a pedagogical reflection that, among other things, allows for an analysis of the current educational landscape and how, from this, a set of proposals can be put forward to ensure that geographical knowledge is meaningful for society.